2015
DOI: 10.1108/ijppm-12-2012-0129
|View full text |Cite
|
Sign up to set email alerts
|

Information technology (IT) productivity paradox in the 21st century

Abstract: Information technology (IT) investment since the 1970s coincided with poor productivity gains: the 'IT productivity paradox'. This phenomenon is still poorly understood. This research replicates methods employed by previous studies for comparability but employs a two-level approach: First macroeconomic indicators; second labor and multi-factor productivity. The findings suggest IT investment has high positive correlation with gross domestic product (GDP) growth, but not labor or multi-factor productivity. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 42 publications
1
42
0
3
Order By: Relevance
“…So far empirical evidence has shown contradictory results which suggest that IT does not necessarily improve performance or enhance business value. Instead, the "IT productivity paradox" exists (Brown, 2015;Brynjolfsson, 1993;Brynjolfsson and Hitt, 1996;Hajli et al, 2015). Some others viewed IT as a commodity which had little distinct value in terms of creating sustainable advantages for firms, instead it is easily imitated by competitors (Carr, 2002;Jean et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…So far empirical evidence has shown contradictory results which suggest that IT does not necessarily improve performance or enhance business value. Instead, the "IT productivity paradox" exists (Brown, 2015;Brynjolfsson, 1993;Brynjolfsson and Hitt, 1996;Hajli et al, 2015). Some others viewed IT as a commodity which had little distinct value in terms of creating sustainable advantages for firms, instead it is easily imitated by competitors (Carr, 2002;Jean et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Intelligence, 2018, 4 (1), [11][12][13][14][15][16][17] 13 Third, it is the fact that banking industry is the most competitive and highly regulated one. It is also a vital industry area because of its role as an intermediary between financial service providers.…”
Section: Umi Muawanah and Gunadi Journal Of Information Systems Engineementioning
confidence: 99%
“…In addition to these facts, other research indicated that the productivity paradox over IT investment still exists considering macroeconomic, labor and multi-factor productivity variables [11]. The paradox states that in spite an increase in the IT investment the promised productivity caused by the IT does not seem to realize.…”
mentioning
confidence: 99%
“…De maneira geral, a gestão dos investimentos deve ser realizada de maneira cautelosa a fim de minimizar os riscos com estes (BROWN, 2015;HAJLI;SIMS, 2015 …”
Section: Investimentos Em Tecnologia Da Informação E Comunicação (Tic)unclassified